Understanding Ecuador’s Generation Z tourist profile - Toledo López, Naun Alexander; Bermúdez Gallegos, Christian; Coronel Pérez, Verónica (Revista Universidad de Guayaquil, 2020)
The tourism industry’s contribution to the economic, social, cultural, and environmental sphere makes it necessary to form new marketing strategies aligned with the use of new technologies since current generations demand it. In this study, the consumption profile of tourists from generation Z will be determined, which is the one with the highest participation in the tourism industry. For this, the quantitative paradigm was accepted, starting from a conceptual model with factors recommended by the literature such as the image of the destination, travel reasons, experiences, and surroundings. These were adapted to the study context and consolidated in a questionnaire that was applied with a cross-section in a sample of 388 tourists from the city of Guayaquil, as it is the one that receives the largest number of tourists per year in Ecuador. With a descriptive scope, the contribution of the different factors in the conceptual model was obtained, the main motivation being to spend vacations with friends, in destinations that have mountains and beaches as attractive, they also like all aspects that generate a positive experience to be shared through of their social networks.